RANCANG BANGUN WEB SEKOLAH DAN IMPLEMENTASI SISTEM PEMANTAUAN KEGIATAN BELAJAR MENGAJAR BERBASIS NIRKABEL - Viving Frendiana; Fitri Elvira Ananda; Mohamad Fathurahman; Dandun Widhiantoro; Agus Wagyana; Asri Wulandari; Zulhelman; Budi Utami (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
This Community Service Activity aims to create a school website and implement monitoring cameras at the SMP Islam NusantaraDepok. School websites can be used by schools as a means of delivering information, promotion, and even learning activities. The more professional and modern the design, the more interested prospective students are to find out more about the school. On the other hand, security is an important factor in supporting a sense of security and comfort in the school environment, especially during teaching and learning activities. Therefore, the implementation of Community-Based Science and Technology Application Service is to design a school web and implement a CCTV-based wireless monitoring system for teaching and learning activities. This empowerment program aims to make schools have informative websites. The existence of a school website is expected to be a medium of information and communication between teachers, students, and guardians of students as well as a means of school branding. In addition, this service also implemented a wireless-based monitoring system for teaching and learning activities. With CCTV monitoring, it is hoped that it can support a sense of security and comfort in order in the school environment, especially during teaching and learning activities.